SAK-EMKM pada Penyusunan Laporan Keuangan bagi Kios Dewi - Hayati, Sari (Universitas Darwan Ali, 2022)
Today's entrepreneurship can be said to be a struggle for prospective workers to overcome the increasing number of unemployed. One of them is by opening a food stall business and so on or trading. This UMKM is a business that is widely developed because basic necessities are a definite food needed in society, no wonder there is a lot of market demand for basic necessities. However, what is still a weakness in this business is that there is no recording of financial statements that have been made since this business started. Therefore, this study aims to help MSMEs at Dewi's kiosk record and prepare finances in accordance with SAK-EMKM. This research uses a descriptive research method that is done by interviews and documentation of transaction evidence. And the results of the study show that the statement of financial position in the form of income is accepted